Prevalence of Metabolic Syndrome among Obese Children and Adolescents (BIRDEM Medical Journal, 2012)
Objectives: The Prevalence and magnitude of childhood obesity are increasing dramatically. The study was undertaken to see the prevalence of metabolic syndrome among children and adolescents with obesity, attending the Paediatric Endocrine OPD, BIRDEM. Methods: A cross sectional study was conducted from January 2006 to December 2008 among obese children and adolescents (6-18 years) attending Paediatric endocrine out patient department of BIRDEM. Children with any other endocrine disorder, dysmorphism/syndrome were excluded. Obesity was defined as BMIe95th percentile for age and sex using CDC growth chart. Children underwent two-hour oral glucose tolerance test, anthropometric and blood pressure measurement. Fasting serum insulin and lipid profile were measured. Impaired glucose tolerance (IGT) was defined as fasting plasma glucose (FPG)